Estado nutricional, atividade física, comportamento sedentário, dieta e estilo de vida associados ou não a doenças respiratórias em crianças - Victo, Eduardo Rossato De [UNIFESP] (2019)
Objective: To assess the association between nutritional status, physical activity and lifestyle of children aged 9 to 11 years with the development of asthma and/or rhinitis after 5 years of follow-up. Methods: This is a retrospective study with Brazilian children belonging to the International Study of Childhood Obesity, Lifestyle and the Environment (ISCOLE). Lifestyle factors (body composition, level of physical activity, diet and environment) were measured in 2012/13. After 5 years, the participants answered the questionnaire from the International Study of Asthma and Allergies in Chilhood (ISAAC) for the diagnosis of possible asthma and / or rhinitis. Logistic regression was performed to identify factors associated with developing asthma and / or rhinitis. Results: The final sample consisted of 168 students (56% boys). The prevalence of asthma and rhinitis in this population was 15.5% and 25.6%, respectively. The factors associated with asthma were: consumption of whole milk (OR = 1.241, 95% CI: 1.033-1.491), having TV in the room (OR = 0.295, 95% CI: 0.122-0.714) and practicing physical education classes two or more times / week (OR = 0.308; 95% CI: 0.116-0.818). For rhinitis the related factors were: female (OR: 2.453; 95% CI: 1.207-4.989) and total milk consumption (OR = 1.213 95% CI: 1.045-1.407). Conclusions: Consumption of whole milk, having TV in the bedroom, amount of physical education classes in the week and sex were factors associated with respiratory diseases. Public policies should be directed at preventing respiratory diseases.